Growth Response of Mucuna bracteata with the Application of Local Micro Organisms (LMO) of Banana Weevil - Pratomo, Bayu; Tanjung, Agung Rafiul Naldi; Aryska, Dini; Ginting, Chelvin Van Roy (Tabela Jurnal Pertanian Berkelanjutan, 2024)
This research aims to determine the effect of concentration and duration immersion giving LOM banana weevil against the gowth of Mucuna bracteata. The research was conducted in the garden of Jalan Setia Bangun Pasar III, Sei Beras Sekata, Kecamatan sunggal, Kabupaten Deli Serdang, Sumatra utara and continued in the laboratory of the Indonesian Oil Palm Research Institute (IOPRI). This research was started in April-June 2020. This study used a randomized complete block design (RCBD) factorial. The first factor was the concentration of local microorganisms (LMO) of Banana Weevil consisting of 4 levels, namely: Without treatment, 15%, 30%, 45%. The second factor. The duration of immersion consists of 4 levels, namely: No immersion time, 15 minutes, 30 minutes, 45 minutes. Observation data were analyzed usingDuncan's Multiple Range Test with a significant 5%. The results showed that the LMO concentration of banana weevil was effective in increasing the gowth of the number of leaves 39.77, tendril length 83.14 cm, shoot fresh weight 28.54 g, and shoot dry weight 6.03 g. The duration of soaking had a significant effect on the highest number of leaves at week 3 (9.63 pieces). The interaction application of banana weevil concentration and soaking time affected the number of root nodules (40.50 gains) and root dry weight (0.73) g of theplant Mucuna bracteata.